Factors predictive of the presence of a CSF1R mutation in patients with leukoencephalopathy. (15th October 2019) - Kondo, Y.; Matsushima, A.; Nagasaki, S.; Nakamura, K.; Sekijima, Y.; Yoshida, K.
Abstract : Background and purpose: The purpose was to identify statistically factors that correlate with the presence of a colony‐stimulating factor 1 receptor ( CSF1R ) mutation and to reevaluate the accuracy of the current diagnostic criteria for CSF1R ‐related leukoencephalopathy. Methods: CSF1R testing was conducted on 145 consecutive leukoencephalopathy cases who were clinically suspected of having adult‐onset leukoencephalopathy with axonal spheroids and pigmented glia. From these, 135 cases whose detailed clinical information was available were enrolled. Forward logistic stepwise regression was performed to generate a probability model to predict a positive CSF1R mutation result. The current diagnostic criteria were also applied to our cohort and their sensitivity and specificity were calculated. Results: Twenty‐eight CSF1R ‐mutation‐positive cases and 107 CSF1R ‐mutation‐negative cases were identified. Our probability model suggested that factors raising the probability of a CSF1R ‐mutation‐positive result were younger onset, parkinsonism, thinning of the corpus callosum and diffusion‐restricted lesions. It also showed that involuntary movements and brainstem or cerebellar atrophy were negative predictors of a CSF1R ‐mutation‐positive result. In our cohort, the sensitivity and specificity for 'probable' or 'possible' CSF1R ‐related leukoencephalopathy were 81% and 14%, respectively. Conclusions: Clinical and brain imaging features predictive of the presence of a CSF1R mutation are proposed. Consideration of these factors will help prioritize patients for CSF1R testing.